What drives yield formation in sugar beet? Quantifying functional components across genotypes and irrigation managements - Finn Großmann; Henning Kage; Dieter Hackenberg; Till Rose (Field Crops Research, 2026)

Leaf protein extractability in sugar beet: Genetic control and breeding potential for dual-purpose cultivars - Hugo Rijken; Aamir Saleem; Christian B. Hirschmann; Dieter Hackenberg; Marieke E. Bruins; Luisa M. Trindade (Field Crops Research, 2026)

Correction: Regulatory dynamics of gene expression in the developing male gametophyte of Arabidopsis - Božena Klodová; David Potěšil; Lenka Steinbachová; Christos Michailidis; Ann-Cathrin Lindner; Dieter Hackenberg; Jörg D. Becker; Zbyněk Zdráhal; David Twell; David Honys (Plant Reproduction, 2023)

Regulatory dynamics of gene expression in the developing male gametophyte of Arabidopsis - Božena Klodová; David Potěšil; Lenka Steinbachová; Christos Michailidis; Ann-Cathrin Lindner; Dieter Hackenberg; Jörg D. Becker; Zbyněk Zdráhal; David Twell; David Honys (Plant Reproduction, 2023)
Sexual reproduction in angiosperms requires the production and delivery of two male gametes by a three-celled haploid male gametophyte. This demands synchronized gene expression in a short developmental window to ensure double fertilization and seed set. While transcriptomic changes in developing pollen are known for Arabidopsis , no studies have integrated RNA and proteomic data in this model. Further, the role of alternative splicing has not been fully addressed, yet post-transcriptional and post-translational regulation may have a key role in gene expression dynamics during microgametogenesis. We have refined and substantially updated global transcriptomic and proteomic changes in developing pollen for two Arabidopsis accessions. Despite the superiority of RNA-seq over microarray-based platforms, we demonstrate high reproducibility and comparability. We identify thousands of long non-coding RNAs as potential regulators of pollen development, hundreds of changes in alternative splicing and provide insight into mRNA translation rate and storage in developing pollen. Our analysis delivers an integrated perspective of gene expression dynamics in developing Arabidopsis pollen and a foundation for studying the role of alternative splicing in this model.

Identification and QTL mapping of resistance to Turnip yellows virus (TuYV) in oilseed rape, Brassica napus - Dieter Hackenberg; Elvis Asare-Bediako; Adam Baker; Peter Walley; Carol Jenner; Shannon Greer; Lawrence Bramham; Jacqueline Batley; David Edwards; Regine Delourme; Guy Barker; Graham Teakle; et al. (Theoretical and Applied Genetics, 2020)
Key message Partially dominant resistance to Turnip yellows virus associated with one major QTL was identified in the natural allotetraploid oilseed rape cultivar Yudal. Abstract Turnip yellows virus (TuYV) is transmitted by the peach-potato aphid ( Myzus persicae ) and causes severe yield losses in commercial oilseed rape crops ( Brassica napus ). There is currently only one genetic resource for resistance to TuYV available in brassica, which was identified in the re-synthesised B. napus line ‘R54’. In our study, 27 mostly homozygous B. napus accessions, either doubled-haploid (DH) or inbred lines, representing a diverse subset of the B. napus genepool, were screened for TuYV resistance/susceptibility. Partial resistance to TuYV was identified in the Korean spring oilseed rape, B. napus variety Yudal, whilst the dwarf French winter oilseed rape line Darmor- bzh was susceptible. QTL mapping using the established Darmor- bzh × Yudal DH mapping population (DYDH) revealed one major QTL explaining 36% and 18% of the phenotypic variation in two independent experiments. A DYDH line was crossed to Yudal, and reciprocal backcross (BC 1 ) populations from the F 1 with either the susceptible or resistant parent revealed the dominant inheritance of the TuYV resistance. The QTL on ChrA04 was verified in the segregating BC 1 population. A second minor QTL on ChrC05 was identified in one of the two DYDH experiments, and it was not observed in the BC 1 population. The TuYV resistance QTL in ‘R54’ is within the QTL interval on Chr A04 of Yudal; however, the markers co-segregating with the ‘R54’ resistance are not conserved in Yudal, suggesting an independent origin of the TuYV resistances. This is the first report of the QTL mapping of TuYV resistance in natural B. napus .